Deciphering the Interplay of Frailty, Age, and Gender in Orthopedic Surgical Outcomes Among the Elderly: Insights From a Prospective Cohort Study - Rushama Tandon MS; Ashutosh Kapoor MS; Rajan Kumar Singh DNB; Anil Kumar Verma DNB; Nand Kishor Kaushale DNB (Geriatric Orthopaedic Surgery & Rehabilitation)
Background: With India’s aging population on the rise, the prevalence of frailty among elderly patients undergoing major orthopedic surgeries presents a significant challenge for healthcare systems. Frailty, characterized by decreased physiological reserve and increased vulnerability to adverse health outcomes, necessitates a comprehensive approach to preoperative evaluation and care. This study aims to explore the correlation between frailty and socio-demographic variables, particularly age and gender, utilizing the Edmonton Frailty Scale (EFS) to assess frailty among elderly orthopedic surgery patients. Material and Methods: A prospective cohort study was conducted, encompassing 157 patients aged 60 years and above, undergoing major orthopedic procedures between June 2019 and June 2021. The EFS was employed to evaluate frailty, categorizing patients across a spectrum from ‘Not Frail’ to ‘Severe Frail’. Statistical analysis was performed to examine the relationship between frailty levels and socio-demographic variables. Results: The majority of participants were males (59.2%) in the age group of 60-65 years (63.7%). The distribution of frailty revealed 40.1% of patients as not frail, with a substantial proportion displaying varying degrees of frailty. A significant correlation was found between increased frailty severity and advancing age ( P < .001), while gender differences in frailty distribution suggested a higher predisposition towards severe frailty among females. Conclusion: The study underscores the high prevalence of frailty among elderly orthopedic patients and its significant association with age and gender. These findings highlight the necessity for frailty-informed preoperative assessments and interventions tailored to the specific needs of elderly patients. Incorporating frailty evaluations into clinical practice can enhance surgical outcomes and improve the quality of care for this vulnerable population.